Differential Patterns of Risk and Vulnerability Suggest the Need for Novel Prevention Strategies for Black Bisexual Men in the HPTN 061 Study. (15th August 2018) - Dyer, Typhanye V.; Khan, Maria R.; Regan, Rotrease; Harawa, Nina T.; Nelson, LaRon E.; Wilton, Leo; Wang, Lei; Peng, Lili; Ou, San San; Shoptaw, Steve
Abstract : Background: Black men who have sex with men (BMSM) and some who also have sex with women (BMSMW) account for over 70% of new HIV infections in the United States representing an elevated HIV risk in this group, also informing risks of HIV transmission to other BMSM and female sexual partners. Settings: We examined trajectories of self-reported substance use, HIV-related sexual risk behaviors, and psychosocial vulnerabilities among BMSMW versus BMSM over a 1-year study period. Methods: We analyzed baseline, 6-, and 12-month follow-up data from the HIV Prevention Trials Network "BROTHERS" Study (HPTN 061; n = 1126). Categorizing participants by sexual partner type across 3 time points: (1) BMSMO: having male and no female partners across assessments and (2) BMSMW: having sex with male and one or more female partners at least at 1 time point. Using generalized estimating equations, we estimated associations between being BMSMW (versus BMSMO) and changes in psychosocial vulnerability, substance use, and HIV-related sexual risk behaviors. Results: Generalized estimating equation models controlling for sociodemographics, time-varying effects, and intervention status showed that BMSMW versus BMSMO had 50% increased odds of crack use, 71% increased odds of alcohol use during condomless anal intercourse (CAI), 51% greater odds of using drugs at last CAI, and twice the odds of receiving goods at last CAI. Conclusions: Findings show stable and comparatively elevated illicit drugs, alcohol, and exchange sex during last CAI among BMSMW. Future intervention research should focus on ways to address changes in substance-related HIV-transmission behaviors over time in this population of men.